The Effect of Green Banking Disclosure on the Financial Performance of Regional-Owned Islamic Banks - Ernawati, Siti; Utami, Cahyaning Budi (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the impact of green banking disclosure on the financial performance of regional-owned Islamic commercial banks in Indonesia. This research employs a quantitative approach and uses secondary data sourced from the sustainability report of the banks starting from 2020 until 2023. The study focuses on four Islamic banks owned by local governments: Aceh Syariah Bank, BJB Syariah Bank, NTB Syariah Bank, and BRK Syariah Bank. The analysis technique used include descriptive analysis and panel data regression analysis. The results showed that GBDI has no significant effect on ROA and ROE. This outcome may be attributed to the fact that many banks are not prioritizing the disclosure of green banking information, especially in countries where regulations on green banking practices are weak. However, adequate disclosure of green banking can improve transparency, accountability and efficiency of banks, potentially leading to a positive impact on their financial performance. Some limitations of this study need to be considered, specifically the research only focuses on regional-owned Islamic commercial banks in Indonesia. Future research could expand the sample to include Islamic commercial banks owned by the central government as well as private Islamic banks to provide more comprehensive insights.